FEATURES SPEECH REHABILITATION IN THE ACUTE STROKE IN DIFFERENT FORMS OF APHASIA - Сафронова, Марина Николаевна; Коваленко, Андрей Владимирович; Мизюркина, Ольга Александровна; Тен, Станислав Борисович (Medicine in Kuzbass, 2018)
Objective. To determine the dependence of speech recovery on the type of aphasia, localization of the focus of ischemia and vascular risk factors in patients with acute ischemic stroke in the carotid basin.Material and methods. 351 patients with ischemic stroke were examined, median age – 61 (55; 72). The degree of speech recovery was characterized by an increase in the score on the scale of the speech questionnaire (ΔSQ) on the 21st day from the onset of the disease. Patients were divided into 2 groups: with a low level of recovery – ΔSQ ≤ 6; with a high level – ΔSQ > 6. Speech disorders were represented by motor and sensorimotor aphasia. The influence of localization of ischemia focus in the brain, arterial hypertension, angina pectoris, myocardial infarction, dyslipidemia, type 2 diabetes mellitus, stenosis of extracranial arteries on aphasia regression was evaluated.Results. The group ΔSQ ≤ 6 was dominated by patients with sensorimotor aphasia: n = 141 (76,6 %). In the group ΔSQ > 6 motor aphasia was more common – 119 people (71,3 %), sensorimotor aphasia was observed in 48 patients (28,7 %) (p = 0,0001). In patients of the group ΔSQ ≤ 6, the ischemic focus more often had cortical-subcortical localization (p = 0,006), groups ΔSQ > 6 – subcortical (p = 0,001). The group ΔSQ ≤ 6 was dominated by patients with a constant form of atrial fibrillation (p = 0,031) and extracranial artery stenosis more than 50 % (p = 0,0001).Conclusions. With a low level of speech restoration function in the acute period of ischemic stroke associated cortical-subcortical ischemic focus, stenosis of the brachiocephalic arteries over 50 % and a constant form of atrial fibrillation, with a high level – speech disorders by type of motor aphasia.
Keywords: aphasia; stroke; speech disorders; stenosis of brachiocephalic arteries; ischemic focus; atrial fibrillation